PERAN ORANG TUA DALAM PEMBELAJARAN DAN PENINGKATAN ASPEK KOGNITIF PADA ANAK USIA DINI - Alquriyah, Yusroh (Tunas Siliwangi, 2025)
Education has a very an important role in human life to build children's future. People education are expected to be able to develop their knowledge, skill, and creativity. The aim of this research is to determine the role of parents in learning activities and improving cognitive aspects in early childhood. This research is field research using a qualitative descriptive approach in describing research results through observation, interviews and documentation analysis to collect data from teachers, students and parents. The results of this research are the role of parents in early childhood learning. The majority of children entering play groups are still dependent on their parents. In children's daily lives, parents will provide children with learning related to new things by providing simple explanations to improve the child's cognitive aspects.